Fenomena Fear Of Missing Out dan Adaptasi Budaya Digital Pada Mahasiswa Gen Z di Isi Padang Panjang - Meisya Nurul Azizah; Basyarul Aziz; Esa Rahmadani (STKIP Subang, 2026)
The development of digital technology has influenced the communication patterns and lifestyles of university students, notably through the phenomenon of Fear of Missing Out (FOMO)—an anxiety triggered by the fear of missing out on information or trends on social media. This study aims to understand how Gen Z students at the Institut Seni Indonesia (ISI) Padang Panjang confront the influence of social media and adapt to FOMO amidst Minangkabau cultural values. The research employs a qualitative descriptive approach with digital ethnography methods, utilizing in-depth interviews, social media observations (Instagram and TikTok), and visual curation of the informants' content. Analysis was conducted using the concept of FOMO by Andrew K. Przybylski et al. and the Theory of Self-Presentation by Erving Goffman. The results indicate that FOMO influences Gen Z students in terms of consumptive behavior on TikTok, self-existence on Instagram, and attachment to online games to maintain social relationships. However, FOMO also yields positive impacts by encouraging Gen Z students to seek inspiration and create artworks that are relevant to contemporary developments. This study concludes that students are able to adapt wisely by exercising self-control, limiting screen time, and filtering digital content to preserve their cultural identity.